1999
DOI: 10.1074/jbc.274.32.22770
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Heme-responsive Transcriptional Activator Hap1 Is a Preexisting Dimer in the Absence of Heme

Abstract: In the absence of heme, Hap1 is associated with molecular chaperones such as Hsp90 and Ydj1 and forms a higher order complex termed HMC. Heme disrupts this complex and permits Hap1 to bind to DNA with high affinity, thereby activating transcription. Heme regulation of Hap1 activity is analogous to the regulation of steroid receptors by steroids, which involves molecular chaperones. Steroid receptors often exist as monomers when associated with molecular chaperones in the absence of ligand but as dimers when ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 34 publications
3
44
1
1
Order By: Relevance
“…In response to haeme, these transcription factors bind to activation sequences of numerous genes encoding functions required for respiration and for controlling oxidative damage (Hon et al, 1999). As with other heat-shock proteins (Segui-Simarro et al, 2003), the transport of HO-1 could involve either interaction of the enzyme nuclear localisation signal with the nuclear pore complex or with other cytoplasmic components that would deliver the protein (Li Volti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In response to haeme, these transcription factors bind to activation sequences of numerous genes encoding functions required for respiration and for controlling oxidative damage (Hon et al, 1999). As with other heat-shock proteins (Segui-Simarro et al, 2003), the transport of HO-1 could involve either interaction of the enzyme nuclear localisation signal with the nuclear pore complex or with other cytoplasmic components that would deliver the protein (Li Volti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Most Zn(II) 2 Cys 6 factors localize constitutively to the nucleus, and consequently transcriptional activation by these factors is regulated in the nucleus at the level of DNA binding 16,17) or by intermolecular or intra-molecular masking of the activation domain. 18,19) AmyR is one of the rare examples of regulated nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…These include Gal4p, Pdr1p, Pdr3p, Put3p, Leu3p, Lys14p, and Hap1p of S. cerevisiae, and PrnA and AlcR of A. nidulans. [8][9][10][11][12][13][14][15] Transcriptional activation by these factors in response to inducing stimuli is controlled by mechanisms acting within the nucleus to modulate DNA binding activity 16,17) or to regulate the accessibility of the transcriptional activation domain. 18,19) A. nidulans AflR and NirA are rare examples of Zn(II) 2 Cys 6 transcription factors that show regulated nuclear localization.…”
mentioning
confidence: 99%
“…Studies have revealed that Hap1 contains several important functional elements and that heme regulation of Hap1 involves the regulation of DNA-binding and transcriptionactivating activities of Hap1 (Figure 2A) [14,[28][29][30][31]. The C6 zinc cluster motif, which is located near the N-terminus, and the dimerization domain mediate Hap1 DNA binding, while the seven heme-responsive motifs (HRMs) and three repression modules (RPMs) are responsible for coupling heme regulation with Hap1 activation (Figure 2, Table 1) [14,29,[31][32][33][34].…”
Section: The Yeast Transcriptional Activator Hap1 Acts As a Key Mediamentioning
confidence: 99%
“…The repression of Hap1 in the absence of heme is mediated by the three RPMs, which promote the formation of a higher order Hap1 complex, containing the molecular chaperones and co-chaperones Hsp90, Hsp70, Sro9 and Ydj1 [28,31,36]. This Hap1 multichaperone complex acts to control transcription in response to heme [14,29,30,34]. Hap1 has seven HRMs that can bind heme and mediate heme activation of Hap1 [29].…”
Section: The Yeast Transcriptional Activator Hap1 Acts As a Key Mediamentioning
confidence: 99%